Pengenalan dan Pembiasaaan Perilaku Hidup Bersih dan Sehat (PHBS) Sejak Dini Pada Siswa TK Dharma Wanita Sebewe - Putri Adekayanti; Lina Eta Safitri; Abdul Hamid (Jurnal Pengabdian Bidang Kesehatan, 2023)
Introduction of Clean and Healthy Living Behavior (CHLB) from an early age is very good for educating and instilling awareness of the importance of cleanliness as an effort to maintain personal health and the environment in an ideal condition, so that we can avoid attacks from various diseases such as diarrhea, worms, toothache, Dengue Hemorrhagic Fever (dengue fever) etc. This community service activity aims to introduce CHLB to Dharma Wanita Sebewe Kindergarten students so that students are able to cultivate a culture of clean and healthy living in the school environment and in the family environment. The activity was attended by 20 students. The introduction to CHLB was carried out using a lecture method using stand-X Banner media and direct practice by giving examples to students with song accompaniment, then students followed and practiced again in turns. The types of CHLB that are exemplified and practiced together with students are: washing hands using soap and running water, brushing teeth properly and correctly and disposing of rubbish by separating organic and inorganic waste. All students were very enthusiastic and active in participating in a series of community service activities from start to finish.